Changing color and intensity of LED lighting across the day impacts on circadian melatonin rhythms and sleep in healthy men. Issue 3 (18th January 2021) - Stefani, Oliver; Freyburger, Marlène; Veitz, Simon; Basishvili, Tamara; Meyer, Martin; Weibel, Janine; Kobayashi, Kumpei; Shirakawa, Yasuhiro; Cajochen, Christian
Abstract: We examined whether dynamically changing light across a scheduled 16‐h waking day influences sleepiness, cognitive performance, visual comfort, melatonin secretion, and sleep under controlled laboratory conditions in healthy men. Fourteen participants underwent a 49‐h laboratory protocol in a repeated‐measures study design. They spent the first 5 hours in the evening under standard lighting, followed by an 8‐h nocturnal sleep episode at habitual bedtimes. Thereafter, volunteers either woke up to static light or to a dynamic light that changed spectrum and intensity across the scheduled 16‐h waking day. Following an 8‐h nocturnal sleep episode, the volunteers spent another 11 hours either under static or dynamic light. Static light attenuated the evening rise in melatonin levels more compared to dynamic light as indexed by a significant reduction in the melatonin AUC prior to bedtime during static light only. Participants felt less vigilant in the evening during dynamic light. After dynamic light, sleep latency was significantly shorter in both the baseline and treatment night while sleep structure, sleep quality, cognitive performance, and visual comfort did not significantly differ. The study shows that dynamic changes in spectrum and intensity of light promote melatonin secretion and sleep initiation in healthy men.